SISTEM MANAJEMEN PERGURUAN TINGGI MODERN - Lantip Diat Prasojo (Dinamika Pendidikan, 2009)
College is civilization of pillar a nation because it's  as the  intellectual strength center. College is  centers science and  technology development. In consequence, college have some functions for example (1)  develop human resource that professional in meaning of expertise level, discipline, sincerity, ethics, accuracy, effective and efficient,' (2)  center of science development;  and (3)   will prepare leaders of nation the future. In other hand, college also needs system of exhaled breath management 21'" century. To develop system of college management   21,h century must concerned about four fundamental matters, that  is: 1)  modern management system; 2) concept of balance scorecard, 3) good governance, 4) keep a breast of Information and Communication Technology (ICT).   Keyword: management  system, modern higher education